IMPLEMENTATION OF SUPERVISION ON PEOPLE'S CROSSING TRANSPORTATION EQUIPMENT (KEMPANG) IN KEPULAUAN MERANTI REGENCY - Afrizal; Afrinaldy Rustam; Martha Hasanah Rustam; Ahmad Khairi (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to identify and analyze the implementation of exposure to the Pedestrian Transport Equipment (Kempang) in the Meranti Islands Regency and to analyze the constraints faced by the local government regarding the implementation of supervision of the Pedestrian Transport Equipment (Kempang) in the Meranti Islands Regency. The type of research used is descriptive research with a qualitative approach. The results of this study indicate that the implementation of supervision carried out by the Meranti Islands Regency Government for cross-Kampang has not been carried out properly or has not been optimal. Starting from planning supervision, implementation of supervision to the evaluation carried out. Therefore, the kempang as a means of public transportation needs serious attention from the Regional Government through the Ministry of Communication and Information, both in terms of budget management and planning programs, bearing in mind that many people depend on the kempang to facilitate their daily activities. Factors hindering the implementation of supervision of the People's Crossing Transport Equipment (Kempang) in Meranti Islands Regency are the absence of a communication forum between the Department of Transportation, kempang owners, and the community in an effort to create safe and comfortable kempang crossing transportation, lack of supporting facilities and infrastructure in the kempang crossing process , there is no seriousness from the Department of Transportation in carrying out supervision, even though the kempang crossing is an alternative transportation used for shopping, work, school and other needs and the local government's lack of attention to public transportation (kempang).